2018
DOI: 10.1055/a-0637-9980
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Exponential ADC (eADC) and Computed DWI (cDWI) for the Detection of Prostate Cancer

Abstract: ZUSAMMENFASSUNG Ziel Direkter Vergleich verschiedener Methoden zur besserenErkennung und Differenzierbarkeit von Prostatakrebs in der diffusionsgewichteten Bildgebung (DWI); Vergleich der Ergebnisse mit originalen DWI-Bildern und konventionellen Apparent Diffusion Coefficient (ADC)-Karten. This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited. dataset exponential ADC maps (eADC), computed DWI images (cDWI), and additionally eADC maps for computed b-values of 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the past few decades, prostate cancer has been at the forefront of global male malignancy mortality 25 . As for the diagnosis of prostate cancer, exponential apparent diffusion coefficient and computed diffusion-weighted imaging are often used 26 . The androgen deprivation therapy is useful in the early stage of prostate cancer, but, after the treatment, the disease can develop into castration-resistant prostate cancer 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, prostate cancer has been at the forefront of global male malignancy mortality 25 . As for the diagnosis of prostate cancer, exponential apparent diffusion coefficient and computed diffusion-weighted imaging are often used 26 . The androgen deprivation therapy is useful in the early stage of prostate cancer, but, after the treatment, the disease can develop into castration-resistant prostate cancer 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI), which is based on Brownian motion, utilizes echo-planar imaging (EPI) sequences, while ADC maps can provide qualitative information. As mentioned in some previous studies, the ADC value has been suggested to be the best parameter for predicting cancer occurrence or measuring lesions before biopsy [ 33 , 34 ]. Studies have shown that endometriotic cysts exhibit a lower ADC value than other functional ovarian cysts [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on improving the DWI and ADC. Sprinkart et al proposed an alternative approach to generating cDWIs and altered ADCs [ 15 ]. They acquired DWIs with b-values of 0, 50, and 800 s/mm 2 and computed DWIs with b-values of 2000 and 3000 s/mm 2 .…”
Section: Discussionmentioning
confidence: 99%